2020
DOI: 10.1039/d0ob01553a
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole modified oligonucleotides: synthesis, hybridization studies and fluorescence properties

Abstract: Synthesis of the novel thiophenyl carbazole phosphoramidite DNA building block 5 was accomplished in four steps using a Suzuki-Miyaura cross-coupling reaction from the core carbazole and was seamlessly accommodated into...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Computational and experimental techniques were used, which combined with the previous knowledge on the phosphodiester bond hydrolysis mechanism (Figure ) have reported consistent results, providing a basic and essential understanding of the process. Importantly, we describe probe candidates with low molecular weights compared with that of previous reports that work efficiently as biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Computational and experimental techniques were used, which combined with the previous knowledge on the phosphodiester bond hydrolysis mechanism (Figure ) have reported consistent results, providing a basic and essential understanding of the process. Importantly, we describe probe candidates with low molecular weights compared with that of previous reports that work efficiently as biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Target ON1-ON5 were synthesized at the 1.0 µmol scale on polystyrene beads (Amersham Biosciences, Piscataway, NJ, USA) using an automated synthesizer Expedite 8909 (PerSeptive Biosystems, Framingham, MA, USA) according to the manufacturer's standard protocol, except for the introduction of 2 -O-propargyl-uridine (U P ) into the ON3-ON5 sequence by the so-called "hand-coupling procedure", previously used by Wengel's group [17]. The stepwise coupling efficiencies were >95% for standard conditions and ∼85% for hand-coupling.…”
Section: Synthesis and Purification Of On1-on5mentioning
confidence: 99%
“…Typically, oligonucleotide-based probes consist of covalently attached fluorescent dyes, including perylene [11], pyrene and phenanthroline [12][13][14][15], or fluorescein [16], which are known to exhibit high fluorescence and can interact noncovalently with dsDNA, e.g., by intercalation or groove-binding, leading to its stabilization. We have previously shown that covalent attachment of a carbazole moiety to the 5 -end of a 9-mer sequence increases the thermal stability of the resulting 9-mer/15-mer dsDNA by +4.2 • C [17]. To date, the effect of the combined attachment of both molecules, an intercalator and cyclen, to double-stranded oligonucleotides on their thermal stability has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Illustrative examples are natural light-harvesting complexes, in which the spatial organization of the chromophores is crucial for an efficient transfer of excitation energy within large protein complexes. , In nanotechnology, DNA is widely used as a structural element for the bottom-up assembly of nanostructures because the scaffold of the DNA duplex serves as a versatile, robust, and yet highly reliable tool of spatial control. The specificity and programmability of nucleic acid folding enables the bottom-up creation of multidimensional structures by the DNA origami approach. Alternatively, DNA nanostructures can be constructed by a self-assembly approach using DNA tiles with sticky ends. Despite their elegance, both approaches face some limitations, because they often require a set of many, even up to hundreds, different DNA sequences to assemble a desired nanostructure . The integration of unnatural nucleotide surrogates into oligonucleotides introduces additional functionality and extends the scope of application of DNA from the biological context to the field of materials sciences. Chemically modified DNA conjugates were shown to form supramolecular polymers with potential applications, e.g., in biomedicine for drug delivery systems or in optoelectronic devices. Recently, we reported the supramolecular assembly of amphiphilic DNA, bearing either phenanthrene or tetraphenylethylene (TPE) hydrophobic ends, into vesicle-shaped objects. , Hydrophobic interactions of DNA sticky ends, as well as spermine-mediated electrostatic interactions, , are among the driving forces that lead to the formation of these DNA-constructed vesicles. Besides serving as sticky ends, hydrophobic TPE overhangs also permit the direct observation of the self-assembly process by fluorescence spectroscopy due to their aggregation-induced emission (AIE) properties. Potential applications of vesicles consisting of a DNA-constructed membrane comprise, among others, the use as delivery vehicles for biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%